Publicité d’intérêt général au Cameroun - Colette Djadeu Nguemedyam (Communication)
Many researchers agree that corruption is one of the main causes of Cameroon’s poverty and lagging social development. The author’s purpose here is to identify the types of communications deployed in the fight against corruption in Cameroon. She begins with an analysis of advertisements from the National Anti-Corruption Commission, then looks at Cameroonians’ perception of them. She then compares those perceptions with the strategies used in order to deduce which arguments are most persuasive in galvanizing public opinion against corruption.